2020
DOI: 10.3390/fluids5040238
|View full text |Cite
|
Sign up to set email alerts
|

Free Flow and Discharge Characteristics of Trapezoidal-Shaped Weirs

Abstract: A number of studies have considered the effects of weir design variations on the free- and submerged-flow characteristics of trapezoidal broad-crested weirs. It appears that the hydraulics of short-crested weir flows have received little attention; thus, the current knowledge is incomplete. By systematically analyzing a large set of experimental data, the present study aims to fill in this knowledge gap and to provide a complete description of the discharge characteristics of trapezoidal-shaped weirs, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…8). Compared to this, the bed-pressure profile of a short-crested weir under free-flow conditions has one absolute minimum pressure near the downstream edge of the weir crest due to the effects of the sharp curvature of the streamline (Zerihun 2020). The result of this analysis confirmed that the bed-pressure profiles exhibit self-similarity only over the upstream face of the weir (see Fig.…”
Section: Bed-pressure Distributionssupporting
confidence: 57%
See 3 more Smart Citations
“…8). Compared to this, the bed-pressure profile of a short-crested weir under free-flow conditions has one absolute minimum pressure near the downstream edge of the weir crest due to the effects of the sharp curvature of the streamline (Zerihun 2020). The result of this analysis confirmed that the bed-pressure profiles exhibit self-similarity only over the upstream face of the weir (see Fig.…”
Section: Bed-pressure Distributionssupporting
confidence: 57%
“…6a). In contrast, the free-flow discharge of a similar short-crested weir significantly increases as the slope of the downstream face increases (Zerihun 2020).…”
Section: Effect Of Downstream-face Slopementioning
confidence: 89%
See 2 more Smart Citations
“…The results show a good fit with the experimental data for ratios 𝐻𝐻 ⁄ between 0 and 5. Moreover, different studies have been carried out in the last five years regarding the analysis of discharge coefficients over particular spillway types, such as: the studies to increase the discharge coefficient in lateral triangular labyrinth weirs by implementing antivortices [36]; the effects of geometric parameters in trapezoidal-triangular labyrinth weirs [37]; the behavior in horizontal crested weirs under free-flow conditions [38]; the variation with respect to discharge coefficients in round-crested weirs [39]; the impact of upstream orientation angle on the discharge coefficient in wide-crested trapezoidal weirs [40]; or, the appropriate use of modeling approaches for the determination of discharge coefficients in lateral rectangular weirs [41] and predictive models [42]. Nevertheless, neither the past or the recent empirical investigation has been studied at high-altitudes, as Condorama.…”
Section: 𝑄=𝐶 𝐿𝐻 /mentioning
confidence: 99%